Investigation of charge transport properties of MoO3 recombination and optical buffer layers in organic and perovskite solar cells - Firdaus Suhaimi (Nanyang Technological University, 2021)
Advances in organic photovoltaic cells (OPV) based on bulk heterojunction (BHJ) devices comprising donor and acceptor material combinations have been intensively researched for their potential as renewable energy sources. In addition to new materials that harvest the solar spectrum more efficiently, novel device concepts and cost effective fabrication techniques are also actively researched to yield higher solar cell efficiencies without any cost penalties. Besides the light-absorbing active layers, charge transport layers like molybdenum trioxide (MoO3), are integral parts in that help reduce the significant energetic mismatch at the interface between the electrodes and the active layers, enhancing charge flow of the devices that have pushed the efficiency of these organic PV devices to beyond 13%. MoO3 is being extensively studied because of its unique electrical characteristics and hole transporting properties in OPV devices. Bulk, stoichiometric MoO3 is typically an insulator but when deposited in thin film form, it is known to be an n-type semi-conductor owing to the oxygen vacancies formed during the deposition processes. When deposited with film thicknesses of 3.5nm to 15nm, MoO3 is reported to be an effective hole transport layer with its electronic and photophysical characteristics comparable to the conventionally used PEDOT:PSS materials. However, charge transport in MoO3 is known to be affected by air exposure, UV ozone pre-treatments and a complete understanding of its structure – property relationships is essential prior to incorporation into high efficiency solar cells.